2011
DOI: 10.1504/ijmsi.2011.041935
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of the Sanctuary of Vicoforte, Italy

Abstract: In order to evaluate safety assessment of the Sanctuary of Vicoforte, Italy, a series of non-destructive tests were carried out for diagnostic inspection of its deterioration. Delamination of stone finishing and fresco painting were detected. Dynamic ambient vibration test was carried out and the relevant modes of vibration were identified resorting to the stochastic subspace identification method. The first two natural frequencies of the Sanctuary of Vicoforte were estimated to be about 1.93 Hz and 2.07 Hz in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In addition the mechanical response of the dome of the Basilica of S. Maria of Carignano is discussed, showing that, as already conjectured by Como (1997), the dome and the drum are not separate structures, simply transferring loads one to the other, but form an interconnected structural system. Such a conclusion is similar to what has been recently found for the elliptical dome of the Santuario of Vicoforte (Aoki et al 2011) and provides some improvement to the technical and scientific literature on this issue (Huerta 2008) that looks at the dome as the main structure (Heyman 1967;1988;Oppenheim et al 1988, Pesciullesi et al 1997O'Dwyer 1999;Fraternali 2010;Zessin 2010;D'Ayala and Tomasoni 2011;among others). In addition, it is showed that the ultimate load-carrying capacity of the dome that is discussed elsewhere (Bacigalupo et al 2012) relying on limit analysis, is not necessarily the main issue for understanding either its mechanical response nor the crack pattern.…”
Section: Introductionsupporting
confidence: 88%
“…In addition the mechanical response of the dome of the Basilica of S. Maria of Carignano is discussed, showing that, as already conjectured by Como (1997), the dome and the drum are not separate structures, simply transferring loads one to the other, but form an interconnected structural system. Such a conclusion is similar to what has been recently found for the elliptical dome of the Santuario of Vicoforte (Aoki et al 2011) and provides some improvement to the technical and scientific literature on this issue (Huerta 2008) that looks at the dome as the main structure (Heyman 1967;1988;Oppenheim et al 1988, Pesciullesi et al 1997O'Dwyer 1999;Fraternali 2010;Zessin 2010;D'Ayala and Tomasoni 2011;among others). In addition, it is showed that the ultimate load-carrying capacity of the dome that is discussed elsewhere (Bacigalupo et al 2012) relying on limit analysis, is not necessarily the main issue for understanding either its mechanical response nor the crack pattern.…”
Section: Introductionsupporting
confidence: 88%
“…More information about the Sanctuary of Vicoforte can be found in [24]. Over the years, the Sanctuary of Vicoforte has been the subject of various types of investigation [24][25][26]. Moreover, the evolution of the damage in the sanctuary has been monitored since 1985, when the first strengthening system was installed [24].…”
Section: The Case Of the Sanctuary Of Vicofortementioning
confidence: 99%
“…Theoretical and experimental investigations implemented on the historical masonry domes can be summarized as follows: (i) theoretical studies under static loads, 1,9,11,13, (ii) theoretical studies under dynamic loads, 8,[61][62][63][64][65] (iii) model tests in laboratory, [66][67][68][69][70] (iv) in situ tests. [71][72][73][74][75][76][77][78] It can be understood from the studies mentioned above that upgrading historical masonry domes is of great importance. Therefore, many studies have been prepared on the strengthening of masonry domes under static and dynamic loads.…”
Section: Work On the Safety And Strengthening Of Masonry Domesmentioning
confidence: 99%
“…Theoretical and experimental investigations implemented on the historical masonry domes can be summarized as follows: (i) theoretical studies under static loads , 1,9,11,13,2260 (ii) theoretical studies under dynamic loads , 8,6165 (iii) model tests in laboratory , 6670 (iv) in situ tests . 7178…”
Section: Work On the Safety And Strengthening Of Masonry Domesmentioning
confidence: 99%
See 1 more Smart Citation